Analysis of Budgetary Slack Indications in the Implementation Effectiveness of the Family Hope Program - Dima, Enike Tje Yustin Dima; Timuneno , Antonius Yohanes William; Baso, Susana Purnamasari; Baso, Maksimilianus Paulus Jati x; Banase, Marianus Antonius Deo Datus (Journal La Sociale, 2025)
This study aims to explore the influence of budgetary slack and implementation effectiveness on the success of the Family Hope Program (PKH) in Buraen Village, South Amarasi District. The problem of high poverty and unequal distribution of PKH assistance recipients is the main background. This study uses a quantitative approach with the Partial Least Squares (PLS) method and involves 84 respondents selected through purposive sampling. The analysis results show that budgetary slack has a positive and significant effect on the success of PKH with a coefficient of 0.677 (p < 0.01), while effectiveness also has a positive effect with a coefficient of 0.202 (p < 0.10). The coefficient of determination (R²) value of 0.735 indicates that 73.5% of the variation in PKH success can be explained by these two variables. These findings indicate that strategically managed budget flexibility and effective program implementation can increase the social impact of PKH, especially in the education, health, and economic aspects of poor households. Therefore, PKH implementing agents have an important role not only as administrative distributors, but also as adaptive decision makers in addressing the dynamics of local needs.